Hypothyroidism in transfusion dependent β-thalassemia - Ayoub, Najla (Iraqi Journal of Cancer and Medical Genetics, 2016)
Background: beta thalassemia major is a big health problem worldwide. There are few studies dealing with prevalence and nature of thyroid dysfunction in Iraq. Objectives: to establish the prevalence of thyroid dysfunction among patients with beta thalassemia major. Patients and Methods: this study was conducted during Nov. 2013 and dealt with 73 Iraqi patients with beta thalassemia major attending Al-Karma thalassemia Centre in Baghdad. They included 40 males and 33 females with age ranged from 15 years to 30 years. The height and weight were measured. Thyroid function tests were performed by enzyme linked fluorescent antibodies. Results: hypothyroidism were reported in 16 patients 10 males and 6 females out of 73 patients examined with prevalence rate of 21.9%. All cases of hypothyroidism were subclinical hypothyroidism (high TSH level with normal T4 and T3).No case was documented to have autoimmune thyroiditis. Conclusion: there is high prevalence of thyroid dysfunction among Iraqi patients with beta thalassemia major. It is of high importance to monitor those patients at yearly intervals for early detection and replacement therapy